2011
DOI: 10.4314/aipm.v9i1.72432
|View full text |Cite
|
Sign up to set email alerts
|

Pattern, indications and review of complications of neonatal blood transfusion in Ibadan, southwest Nigeria

Abstract: Background and objectives:There is a huge need for blood transfusion in the newborn particularly due to the reduced marrow activity in the neonatal period. Despite widely use of blood products in the neonatal period, there is paucity of local data on the pattern, indications and reactions to blood transfusions in Nigerian newborns. This study evaluates the blood transfusion indications and patterns in special care baby unit and C12nd of University College Hospital, Ibadan, Nigeria.Methodology:A cross sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 15 publications
7
19
1
Order By: Relevance
“…The commonest indication for transfusion was severe neonatal jaundice. This is 5,6,12,13 similar to the experience of some other centres. The prevalence of blood transfusion was 11.0% in the present study and similar to 11.7% reported by Joel-…”
Section: Discussionsupporting
confidence: 85%
“…The commonest indication for transfusion was severe neonatal jaundice. This is 5,6,12,13 similar to the experience of some other centres. The prevalence of blood transfusion was 11.0% in the present study and similar to 11.7% reported by Joel-…”
Section: Discussionsupporting
confidence: 85%
“…It is however higher than the 11.7% documented from another hospital in Ogbomosho, still in south-western Nigeria [16] and studies by Pam et al in Jos, northern Nigeria which documented 16.5% neonatal transfusions. It is lower than the 30.8% reported by Ayede et al [17].…”
Section: Resultscontrasting
confidence: 58%
“…Two studies (3%) identified a febrile nonhemolytic transfusion reaction (FNHTR) as an outcome with samples of 100 and 110 transfusion events examined . Both studies were prospective observational studies performed in developing countries.…”
Section: Resultsmentioning
confidence: 89%